2022
DOI: 10.1155/2022/1329380
|View full text |Cite
|
Sign up to set email alerts
|

Klotho Ameliorates Podocyte Injury through Targeting TRPC6 Channel in Diabetic Nephropathy

Abstract: Podocyte damage is vital for the etiopathogenesis of diabetic nephropathy (DN). Klotho (KL), a multifunctional protein, has been demonstrated to have renoprotective effects; nevertheless, the mechanism for protective effect has not been completely elucidated. Transient receptor potential cation channel subfamily C, member 6 (TRPC6), a potential target of KL, is implicated in glomerular pathophysiology. Here, we sought to determine whether KL could protect against podocyte injury through inhibiting TRPC6 in DN.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Nonspecific overexpression of TRPC6 in mice has been linked to transient proteinuria [ 35 ]. Increased TRPC6 expression has also been observed in the renal tissues of IMN nephropathy patients and animal models [ 36 ]. TRPC6 expression plays a pivotal role in podocyte injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonspecific overexpression of TRPC6 in mice has been linked to transient proteinuria [ 35 ]. Increased TRPC6 expression has also been observed in the renal tissues of IMN nephropathy patients and animal models [ 36 ]. TRPC6 expression plays a pivotal role in podocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, Klotho may be an effective target for the treatment of podocyte injury and confer renoprotection. An accumulating body of evidence supports the renoprotective effects of Klotho in diabetic podocytes [10][11][12][13]. However, it remains unclear whether Klotho can mitigate C5b-9-induced podocyte injury and stabilize the podocyte cytoskeleton in IMN.…”
Section: Introductionmentioning
confidence: 99%
“…It restored the expression of nephrin and ZO-1 and attenuated the increased TRPC6 expression [ 218 ]. A subsequent study found that klotho protected against podocyte cytoskeleton disruption and podocyte injury in DKD by significantly inhibiting the expression of TRPC6 [ 219 ]. These studies provide evidence that klotho is a potential therapeutic strategy for treating DKD by preserving the podocyte cytoskeleton.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Glucose causes diabetic nephropathy by activating the renin-angiotensin system, leading to glomerular foot cell damage [40].Another similarly argues that the angiotensin II/TRPC6/NFAT axis is the treatment for diabetic nephropathy [41].KL inhibits TRPC6 expression, attenuates glycogenic kidney podocyte injury, and reduces proteinuria [42].…”
Section: Trpc6 and The Diabetic Nephropathymentioning
confidence: 99%